Causality Testing and Co-integration between Inflation Rates and Economic Growth in Algeria - SAYAH and KHERBOUCHE, Fatima - Mustapha (International Journal of Engineering Research and Management (IJERM ) Inde., 2016)
Abstract— the main purpose of this study is to examine the relationship between inflation rates and economic growth in Algeria during the period 1991-2013, using the methodology of the Co-integration, causality test. The research found that the time series of the inflation rate and the GDP is non-stationary, and to make it stationary the first differences are applied. So the time series is integrated of the first orders and through the use of Johanson test we found that there is relationship co-integration between inflation rates and economic growth in Algeria, and causal relationship in one direction between them.
Keywords: SOCIAL SCIENCES